Implementation of the Pancasila Student Profile Dimensions of Faith, Fear of Almighty God and Noble Morals in Class 2 Elementary School Pancasila Education Learning - Fauziah, Nida; Hakim, Zerri Rahman; Setiawan, Sigit (Jurnal Pendidikan Amartha, 2025)
This research aims to determine the teacher's efforts, challenges, and impact of implementing the Pancasia Student Profile dimension of faith and devotion to God Almighty. The method used is qualitative descriptive. This research was conducted at SDN Kubang Sepat 1 Cilegon City with research subjects namely teachers, school principals and class II students. Data collection using interview, observation and documentation techniques. To analyze the data using data reduction, then presenting the data, and drawing conclusions. The results found from this research are that teachers have made optimal efforts to implement the Pancasia Student Profile dimension of having faith in being devoted to God Almighty and having noble morals, starting from planning by making learning designs, implementing learning in the form of learning activities that are linked to the dimensions of having faith in being devoted to God Almighty and having good morals. noble, up to learning evaluations in the form of student evaluations and teacher reflections. The challenge faced by teachers is that there are still students who chat during learning activities. Students are also able to display attitudes that are in accordance with the elements in this dimension, namely elements of religious morals during prayer activities, tadarus, and reading Asmaul Husna. The personal element is wearing a uniform according to the regulations, the moral element towards humans which is visible when sharing with each other, the moral element towards nature when throwing away rubbish, and the national element in the form of respecting each other's differences.